2020
DOI: 10.1111/hel.12749
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for recurrence of Helicobacter pylori infection after successful eradication in Chinese children: A prospective, nested case‐control study

Abstract: Background Limited research has been published on the recurrence of Helicobacter pylori infection and risk factors in Chinese children. Our study aimed to identify risk factors for Helicobacter pylori infection recurrence after successful eradication in children. Materials and Methods A prospective, nested case‐control study was performed. A cohort of 230 children with successful eradication of Helicobacter pylori in Baoding (China) was selected from January 2018 to February 2019. A standardized questionnaire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
3
2
0
Order By: Relevance
“… 17 A previous research by the members of our Research Group also revealed that the recurrence rate of Hp-infected children in the region was 18.8% after one year of successful eradication. 18 In the present study, the one-year recurrence rate in this region was 20.4%, which was consistent with previous reports, which may be explained by the underdevelopment of the local economy.…”
Section: Discussionsupporting
confidence: 93%
“… 17 A previous research by the members of our Research Group also revealed that the recurrence rate of Hp-infected children in the region was 18.8% after one year of successful eradication. 18 In the present study, the one-year recurrence rate in this region was 20.4%, which was consistent with previous reports, which may be explained by the underdevelopment of the local economy.…”
Section: Discussionsupporting
confidence: 93%
“…Drinking and dining out were independent risk factors of H. pylori recurrence. Consistent with this study, Zhang et al. (2020a) also reported a high annual H. pylori recurrence rate (18.8%) among children.…”
Section: Helicobacter Pylori Recurrencesupporting
confidence: 88%
“…Drinking and dining out were independent risk factors of H. pylori recurrence. Consistent with this study, Zhang et al (2020a) also reported a high annual H. pylori recurrence rate (18.8%) among children. The follow-up of these two studies was short (1 year) and the enrolled patients were limited to one region.…”
Section: Introductionsupporting
confidence: 88%
“…However, in low socio-economic situations, reinfection can be as high as 23 %. Genetic factors may also play a role and susceptible individuals in whom H. pylori has been eradicated may be prone to reinfection when they are exposed to H. pylori-positive people (16,18). Recurrence during the first 3-12 months after cure is mostly due to failed eradication attempts (19).…”
Section: Strong Recommendation (100% Of Agreement) High Quality Evidencementioning
confidence: 99%